Avaliação do impacto da presença de helmintos intestinais na resposta imune celular contra o Mycobacterium tuberculosis em pacientes com tuberculose pulmonar - Có, Tatiana de Resende (2006)
The cellular immune response probably plays a pivotal role in determining the clinical outcome after exposure to Mycobacterium tuberculosis (MTB). This immune response is mediated by Th1 cells, with production of IFN-g, the major cytokine in macrophage activation and mycobacteria eradication. Several factors can be related to tuberculosis resistance. We investigated the role of intestinal helminth infection on M. tuberculosis specific immune response during active tuberculosis in patients with concomitant tuberculosis and intestinal helminth infection at the time of diagnosis and during tuberculosis therapy. Forty patients with newly diagnosed tuberculosis were enrolled in this study. Twenty-seven percent of these patients were co-infected with at least one intestinal helminth (TB+Helminths patients). Concomitant intestinal helminth infection and tuberculosis had a negative impact on absolute numbers of total lymphocytes, B cells, T cells (CD4+ and CD8+), and NKT cells. These alterations were also accompanied by lower IFN-g and elevated and sustained IL-10 levels in whole blood cultures from TB+Helminths patients as compared to TB patients. In addition to a depressed anti-MTB immunity, TB+Helminths patients also presented more severe radiological pulmonary disease, with significant difference in the number of involved lung zones at the end of tuberculosis treatment. The data from this study indicated that intestinal helminth infection can disturb the protective immune response in patients with tuberculosis.